2001
DOI: 10.1046/j.1365-8711.2001.04348.x
|View full text |Cite
|
Sign up to set email alerts
|

The blazar GB 1428+4217: a warm absorber at z = 4.72?

Abstract: BeppoSAX observations of the high‐redshift (z=4.72) blazar GB 1428+4217 confirm the presence of a complex soft X‐ray spectrum first seen with the ROSAT PSPC. Flattening below a rest‐frame energy of 5 keV can be accounted for by absorption from an equivalent column density of (cold) gas with NH∼8×1022 cm−2. Below 2 keV a (variable) excess of a factor of ∼20 above the extrapolated absorbed spectrum is also detected. These findings are consistent with and extend to higher redshifts the correlation between increas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 19 publications
4
40
1
Order By: Relevance
“…Previous X‐ray observations have suggested the presence of soft X‐ray spectral flattening 1 in some radio‐loud quasars at redshifts z = 2–3 (Wilkes et al 1992; Elvis et al 1994; Cappi et al 1997; Fiore et al 1998; Yuan & Brinkmann 1999; Reeves & Turner 2000). This result is strengthened and extended to higher redshifts by its detection in a few extremely X‐ray/radio‐loud quasars at z > 4, namely RX J1028.6 – 0844 (Yuan et al 2000), GB 1428 + 4217 (Boller et al 2000; Fabian et al 2001b), and PMN J0525 − 3343 (Fabian et al 2001a), with ROSAT , ASCA , and BeppoSAX . These object seem to have characteristics typical of blazars (Fabian et al 1997, 1998; Zickgraf et al 1997; Moran & Helfand 1997; Hook & McMahon 1998).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Previous X‐ray observations have suggested the presence of soft X‐ray spectral flattening 1 in some radio‐loud quasars at redshifts z = 2–3 (Wilkes et al 1992; Elvis et al 1994; Cappi et al 1997; Fiore et al 1998; Yuan & Brinkmann 1999; Reeves & Turner 2000). This result is strengthened and extended to higher redshifts by its detection in a few extremely X‐ray/radio‐loud quasars at z > 4, namely RX J1028.6 – 0844 (Yuan et al 2000), GB 1428 + 4217 (Boller et al 2000; Fabian et al 2001b), and PMN J0525 − 3343 (Fabian et al 2001a), with ROSAT , ASCA , and BeppoSAX . These object seem to have characteristics typical of blazars (Fabian et al 1997, 1998; Zickgraf et al 1997; Moran & Helfand 1997; Hook & McMahon 1998).…”
Section: Introductionmentioning
confidence: 76%
“…The most plausible explanation for this effect is photoelectric absorption of soft X‐rays by an associated medium with column densities of 10 22–23 cm −2 , although intrinsic spectral flattening cannot be excluded. The physical implication of this effect has been discussed extensively in the literature in terms of excess absorption (Elvis et al 1998; Yuan et al 2000; Fabian et al 2001a,b) and intrinsic breaks in the X‐ray spectra of blazars (Fabian et al 2001a,b).…”
Section: Introductionmentioning
confidence: 99%
“…According to our model, the peak of the high‐energy hump of the SED during the Beppo SAX observations (Fabian et al 2001) is predicted to lie at ∼1 MeV, locating this source at one extreme of the blazar sequence. The model assumes a black hole mass M = 1.5 × 10 9 M ⊙ , an accretion disc emitting at ∼2/3 of the Eddington ratio (the other third is emitted by the X‐ray corona).…”
Section: Some Illustrative Examplesmentioning
confidence: 87%
“… Top panel: the SED of one of the most distant blazars, together to three different models with different R diss (see Table 1 for the set of parameters) to illustrate possible different states of the source. See Fabian et al (2001) and references therein for the sources of data, and Celotti et al (2007) for further discussion about this source. …”
Section: Some Illustrative Examplesmentioning
confidence: 99%
“…the location of the peak 1 Fossati et al (1998) showed that blazar SEDs seem to change systematically with luminosity; the most powerful objects are red, while blue SEDs are associated with relatively weak sources, a result supported by studies of high‐redshift blazars and of low‐power BL Lac objects (see Costamante et al 2001; Fabian et al 2001a,b; Ghisellini et al 2010).…”
Section: Introductionmentioning
confidence: 94%